The U.S. and The ICC: No More Excuses - Jordan J. Paust (Washington University Global Studies Law Review, 2013)
More than fourteen years after its creation and twelve years after it began to function, the International Criminal Court (“ICC”) still does not have direct support from the United States as a party to its constitutive instrument. There had been prior excuses for the U.S. not becoming a party to the Rome Statute. For example, it had been claimed that there might be unfounded or politicized prosecutions involving unprofessional prosecutors and judges and that a new definition of aggression that could later be created might prevent the United States from using armed force that is permissible under the United Nations Charter. Others had thought that by not becoming a party to the treaty, the U.S. could assure that U.S. nationals would not be prosecuted before the ICC. Are any of these excuses valid today, whether or not they had been previously?
Keywords: international criminal court; ICC; jurisdiction; United States; Rome Statute; party to treaty